2015
DOI: 10.3402/meo.v20.28133
|View full text |Cite
|
Sign up to set email alerts
|

Helping medical students to acquire a deeper understanding of truth-telling

Abstract: ProblemTruth-telling is an important component of respect for patients’ self-determination, but in the context of breaking bad news, it is also a distressing and difficult task.InterventionWe investigated the long-term influence of a simulated patient-based teaching intervention, integrating learning objectives in communication skills and ethics into students’ attitudes and concerns regarding truth-telling. We followed two cohorts of medical students from the preclinical third year to their clinical rotations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
1
12
0
9
Order By: Relevance
“…Regarding teaching techniques, the most valuable methods seem to be the adoption of mixed strategies because it involves different types of approaches, which is favorable in the process of making memories. It is also consistent with the results of various studies 8,21,22,[39][40][41][42][43][44][45][46][47][48][49][50][51] . Nevertheless, a direct comparison between different methods cannot offer a definitive conclusion about the subject, because they only suggest but do not definitely demonstrate the best one.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding teaching techniques, the most valuable methods seem to be the adoption of mixed strategies because it involves different types of approaches, which is favorable in the process of making memories. It is also consistent with the results of various studies 8,21,22,[39][40][41][42][43][44][45][46][47][48][49][50][51] . Nevertheless, a direct comparison between different methods cannot offer a definitive conclusion about the subject, because they only suggest but do not definitely demonstrate the best one.…”
Section: Discussionsupporting
confidence: 92%
“…A shared point of several strategies was the presence of feedback 13,[31][32][33][34][35]39,42,47,48 , which the students thought was of great value. Moreover, there is evidence that the feedback itself is a form of learning, because it allows students to understand and reflect on their mistakes 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(). Communication skills and empathy were essential for a nurse to support patients through all phases of care (Hurst, Baroffio, & Burn, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, 34 (57%) of the studies gathered information from the learners on their reaction to the use of SPs during communication training . Overall, learners reported satisfaction with training, with one study reporting that although the learners were not looking forward to it, they reported finding the process helpful .…”
Section: Resultsmentioning
confidence: 99%